MISCELLANEOUS SOUTH EAST ASIAN CUCURBIT NEWS II - W. J. J. O. DE WILDE & B. E. E. DUYFJES - - (Research Center for Biology, 2009)
DE WILDE, W.J.J.O & DUYFJES, B.E.E. 2009. Miscellaneous South East Asian Cucurbit news II. Reinwardtia 12(5): 405–414. — This paper contains corrections, additions, new taxa, or new records in several genera, which became apparent since previous publications by the authors in these genera.(1) Diplocyclos (Endl.) Post & Kuntze: a new variety in Diplocyclos palmatus (L.) C. Jeffrey(2). Pilogyne Schrad.: re-instatement of this genus name for SE Asian species formerly in Zehneria Endl., with the description of a new species from the Philippines(3) Thladiantha Bunge: Thladiantha nudiflora Forbes & Hemsley, new for Malesia(4) Trichosanthes L.: three subspecies in Trichosanthes tricuspidata Lour.